Socio-Religious Values in Community-Based Islamic Education: A Case Study of Majlis Dzikir in Indonesia - Ahmad Luqman Hakim; Muhammad Arif Syihabuddin (Journal of Education and Religious Studies, 2026)
Community-based religious gatherings such as majlis dzikir have long played an important role in the transmission of Islamic values within Muslim societies. However, their educational function as a medium of non-formal Islamic education has received limited scholarly attention. This study examines the internalization of Islamic educational values in the Majlis Dzikir Fitrah Al-Fahmi community located in Gawerejo Village, Karangbinangun District, Lamongan Regency. Using a qualitative case study approach, the research explores how spiritual, moral, and social values are cultivated through collective dhikr practices and religious interaction. Data were collected through participatory observation, in-depth interviews with twelve informants including the mursyid, community religious figures, and active congregation members and document analysis. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that Majlis Dzikir Fitrah Al-Fahmi functions as a dynamic model of community-based Islamic education in which the values of tauhid, worship, morality, and social solidarity are internalized through spiritual habituation, exemplary leadership, dialogical learning, and communal participation. These practices foster character formation, spiritual awareness, and social responsibility among participants. The study contributes to the discourse on Islamic education by demonstrating that informal religious assemblies can serve as effective spaces for character education and value internalization beyond formal educational institutions. The findings also suggest practical implications for educators and community leaders in developing participatory and spiritually grounded models of Islamic character education within contemporary society.